Aflatoxinas en maíz de clima medio y cálido, cosechado en Cundinamarca durante 1983. I. Incidencia y niveles de contaminación - Carpintero de Jimeno, Martha; Peña B., Néstor E. (Instituto Colombiano Agropecuario, 2019)
In Cundinamarca corn producing area of warm climate study was performed during 1983, in order to establish the incidence of aflatoxin contamination. The levels of contamination and the influence of grain humidity percentage were determinated. From a total of 157 samples collected, 100 on the first semester, 50% (50 samples) of them showed natural contamination with B,, B2 and G, aflatoxins. From the 57 samples taken on the second semester, 29.8% (17 samples) presented the same type of contamination. No G2 aflatoxin levels were detected in any of the analysed samples. The contamination levels varied between less than 15 ug/kg and more than 100 ug/kg. In relation to the grain humidity percentage on the aflatoxin contamination process, 12 to 12.9% interval showed the highest mean levels, 81.9 and 203.5 ug/kg for the first and second semester, respectivelly.